New tuberculosis vaccine to support tuberculosis elimination - Chondro, Fransisca (Faculty of Medicine, Trisakti University, 2018)
The Sustainable Development Goals have prioritized ending the epidemic of tuberculosis by 2030.(1) Around one-third of the world population is infected with Mycobacterium tuberculosis (MTBC), but is asymptomatic, a conditon known as latent TB.According to the global tuberculosis report, in 2017 there were 5-15% of 1.7 billion Â persons infected with MTBC, who will develop TB in their lives. Around 10% of latent TB will develop into active TB disease, with a higher risk in patients with immunodeficiencies such as HIV, undernutrition, diabetes mellitus, smoking, and habitual alcohol consumption. As a result there are annually an estimated 8.8 million new TB cases, with a TB mortality of 1.1 million and deaths from TB and HIV coinfection of 350 thousand cases.The World Health Organization has planned a number of strategies for TB elimination in the year 2030, such as developing rapid and accurate diagnostic tests, new regimens for the treatment of drug-susceptible or drug-resistant TB, prevention of transmission of M. tuberculosis through infection control, new vaccine candidates to prevent the development of TB, and to help improve the outcomes of treatment for TB disease.